Synthesis, Structural Characterization, Hirschfeld Surface Analysis and Photocatalytic CO2 Reduction of Yb(III) Complex with 4-Aacetylphenoxyacetic Acid and 1,10-Phenanthroline Ligands - Xi-Shi Tai; Yuan-Fang Wang; Li-Hua Wang; Xi-Hai Yan (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
A new nine-coordinated Yb(III) complex [YbL3(Phen)] (1) (HL = 2-(4-acetylphenoxy)acetic acid (APA), Phen = 1,10-phenanthroline) was synthesized with 2-(4-acetylphenoxy)acetic acid, YbCl3.6H2O, NaOH and 1,10-phenanthroline as materials. Complex (1) was characterized by IR and X-ray single-crystal diffraction analysis. The results show that the Yb(III) ion is nine-coordinated with seven carboxylate oxygen atoms from five different deprotonated APA ligands and two nitrogen atoms from one Phen ligand. Complex (1) forms a 3D supramolecular framework through the - stacking interactions between the Phen aromatic rings. The hirschfeld surface analysis of complex (1) was also calculated. The CO2 photoconversion activity of complex (1) has been performed under UV-vis light irradiation. The complex (1) shows good photocatalytic activity with the yield of CO is closed to 146 mmol/g after three hours of UV-vis light irradiation, the CO selectivity has reached to 97.9%. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).